Essential requirement of an invariant V alpha 14 T cell antigen receptor expression in the development of natural killer T cells. - Taniguchi, M (1996)
NK1.1+ T [natural killer (NK) T] cells express an invariant T cell antigen receptor alpha chain (TCR alpha) encoded by V alpha 14 and J alpha 281 segments in association with a limited number of V betas, predominantly V beta 8.2. Expression of the invariant V alpha 14/J alpha 281, but not V alpha 1, TCR in transgenic mice lacking endogenous TCR alpha expression blocks the development of conventional T alpha beta cells and leads to the preferential development of V alpha 14 NK T cells, suggesting a prerequisite role of invariant V alpha 14 TCR in NK T cell development. In V beta 8.2 but not B beta 3 transgenic mice, two NK T cells with different CD3 epsilon expressions, CD3 epsilon(dim) and CD3 epsilon(high), can be identified. CD3 epsilon(high) NK T cells express surface V alpha 14/V beta 8 TCR, indicating a mature cell type, whereas CD3 epsilon(dim) NK T cells express V beta 8 without V alpha 14 TCR and no significant CD3 epsilon expression (CD3 epsilon(dim)) on the cell surface. However, the latter are positive for recombination activating gene (RAG-1 and RAG-2) mRNA, which are only expressed in the precursor or immature T cell lineage, and also possess CD3 epsilon mRNA in their cytoplasm, suggesting that CD3 epsilon(dim) NK T cells are the precursor of V alpha 14 NK T cells.